2020
DOI: 10.1101/2020.07.29.227405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polygenic Risk Score for Smoking is associated with Externalizing Psychopathology and Disinhibited Personality Traits but not Internalizing Psychopathology in Adolescence

Abstract: ImportanceLarge consortia of genome wide association studies have yielded more accurate polygenic risk scores (PRS) that aggregate the small effects of many genetic variants to characterize the genetic architecture of disorders and provide a personalized measure of genetic risk.ObjectiveWe examined whether a PRS for smoking measured genetic risk for general behavioral disinhibition by estimating its associations with externalizing and internalizing psychopathology and related personality traits. We examined th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Even though this requires further testing, it could provide some initial evidence that the association between the maternal smoking GRS and offspring externalising problems is more likely to be pleiotropic than confounded by maternal depression. Further, other studies suggest that the genetic instrument for smoking initiation may not only measure smoking behaviour but also capture novelty‐seeking and impulsive behaviours even when only using genome‐wide significant SNPs [ 41 , 45 , 46 , 47 ]. In addition, GSCAN summary statistics for smoking initiation showed a strong genetic correlation with ADHD and risk tolerance behaviour, which could make pleiotropic effects more likely [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though this requires further testing, it could provide some initial evidence that the association between the maternal smoking GRS and offspring externalising problems is more likely to be pleiotropic than confounded by maternal depression. Further, other studies suggest that the genetic instrument for smoking initiation may not only measure smoking behaviour but also capture novelty‐seeking and impulsive behaviours even when only using genome‐wide significant SNPs [ 41 , 45 , 46 , 47 ]. In addition, GSCAN summary statistics for smoking initiation showed a strong genetic correlation with ADHD and risk tolerance behaviour, which could make pleiotropic effects more likely [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…ADHD/conduct disorder in childhood with extraversion & anger personality traits in mothers outside of pregnancy). Third, many mental health phenotypes in childhood were based on maternal report, which may not accurately reflect offspring’s mental health problems (48,49) but rather mothers own mental health status (50,51). Fourth, we constructed PRS for smoking initiation based on the latest GWAS that included ALSPAC mothers (26).…”
Section: Discussionmentioning
confidence: 99%
“…Even though this requires further testing, it could provide some initial evidence that the association between the maternal smoking GRS and offspring externalising problems is more likely to be pleiotropic than confounded by maternal depression. Further, other studies suggest that the genetic instrument for smoking initiation may not only measure smoking behaviour but also capture novelty-seeking and impulsive behaviours even when only using genome-wide significant SNPs (41,4547). In addition, GSCAN summary statistics for smoking initiation showed a strong genetic correlation with ADHD and risk tolerance behaviour, which could make pleiotropic effects more likely (25).…”
Section: Discussionmentioning
confidence: 99%
“…Using the same sample as in this report, we have also shown that these non‐specific effects extend beyond substance use to include externalizing problems (rule‐breaking and aggression) from ages 11 to 17 years (i.e. prior to peak substance use), even after adjusting for contemporaneous nicotine use [40]. The notion of common genetic influences across substances is also consistent with multivariate twin studies that posited a common genetic etiology to account for the co‐occurrence and family transmission of substance use problems, antisocial behavior and disinhibited personality traits [41–43].…”
Section: Discussionmentioning
confidence: 90%